VAGINOSIS BAKTERIALIS DENGAN KOINFEKSI KANDIDIASIS VULVOVAGINALIS - Ellistasari, Endra Yustin; Widyastuti, Zilpa; Kasmitasari, Fitri; Wuri P, Adelia (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Background : Bacterial vaginosis (BV) is an infection caused by an imbalance in the amount of normal vaginal flora and pathogenic bacteria. Vulvovaginal candidiasis (VVC) is an infection of candida in the vagina and vulva. Bacterial vaginosisis often accompanied by co-infection of VVC, it is caused by a reduction in the enzyme hydrogen peroxidase (H2O2) which can reduce the ability of leukocytes to fight infections, resulting in co-infection with other pathogens such as Candida sp. Factors that influence VB with co-infection of VVC include lack of hygiene, changing partners, the use of contraceptives in the uterus, the use of antiseptics with fragrances and other diseases such as diabetes mellitus. Case: A 40-year-old woman complaints of vaginal discharge since 3 months, white-gray vaginal discharge, fishy smell, no itching, and no pain during sexual intercourse. Physical examination revealed the presence of vulvar erythema, yellowish white discharge on the vaginal wall and portio cervicalis. Examination of 10% KOH showed the presence of pseudohyphae. Gram examination showed polymorphonuclear cells >50 per large field of view, gram negative rods 75-100 per large field of view, and clue cells >50%. The patient was given metronidazole 500 mg tablet twice a day for 14 days and fluconazole 150 mg single dose. Clinical and laboratory improvement was found on day 7 and recovered on day 14 after administration of therapy. Discussion: Bacterial vaginosis is an infection caused by the growth of anaerobic organisms that causes high morbidity due to their recurrence rate. This infection is often accompanied by a fungal infection such as kandidiasis vulvovaginalis caused by bad hygiene and increased humidity in genital area. The exact diagnosis of VB along with VVC is based on clinical symptoms, microscopic examination and culture. Antibiotics and antifungal drugs are the mainstay therapies for VB with co-infection of VVC.